A 4arm-PEG macromolecule crosslinked chitosan hydrogels as antibacterial wound dressing. (1st February 2022) - Lu, Jiawei; Chen, Yi; Ding, Meng; Fan, Xiaokun; Hu, Jiawei; Chen, Yihua; Li, Jie; Li, Zhihan; Liu, Wenyong
Abstract: In order to develop better wound dressings, a novel chitosan hydrogel (Cn-Nm gel) was designed and fabricated by using aldehyde-4-arm polyethylene glycol (4r-PEG-CHO) to crosslink the chitosan dissolved in alkaline solution, amino-4-arm polyethylene glycol (4r-PEG-NH2 ) was chosen as the additive simultaneously. The special dissolution technique and macromolecular crosslinking structure endows the Cn-Nm gels with better performance than that of gels prepared by acid dissolving method with micromolecule crosslinker. First, Cn-Nm gels own strong toughness with 500 kPa tensile strength and 1000% elongation, about 400% swelling ratio and fast water absorption rate. Second, about 300 kPa adhesive strength and strippability between the gels and skin is achieved. More importantly, Cn-Nm gels show nearly 100% antibacterial rate towards Escherichia coli and Staphylococcus aureus . Excellent biocompatibility is also proved by the mouse fibroblasts tests. All of the performance makes this developed chitosan-based gel be the potential candidate as a wound dressing.